Six new species of Cladosporium associated with decayed leaves of native bamboo (Bambusoideae) in a fragment of Brazilian Atlantic Forest - Costa, Pricila P.; Rosado, André W. C.; Pereira, Olinto L. (Phytotaxa, 2022)
The Atlantic Forest has the greatest diversity of plants per hectare, and it is considered the main center of bamboo biodiversity in the world. Studies on bambusicolous fungi are scarce and concentrated in temperate regions. Cladosporium is one of the largest genera of dematiaceous hyphomycetes fungus and their adaptation to different environments allows them to have a broad lifestyle. Currently, this genus has been taxonomically and phylogenetically elucidating with the help of extensive polyphasic analyzes. This study aimed to characterize 17 Cladosporium isolates associated with decayed leaves of three bamboo species at a fragment of the Brazilian Atlantic Forest, namely “Parque Estadual da Serra do Brigadeiro”, Minas Gerais state, Brazil. Phylogenetic studies revealed that all isolates belong to the C. cladosporioides species complex. Six new Cladosporium species were found and named herein as C. aulonemiae, C. bambusicola, C. benschii, C. brigadeirensis, C. chusqueae and C. pseudotenuissimum. This study contributes with several taxonomic novelties for knowledge about the diversity of the C. cladosporioides species complex.